Electrical Actuation of Textile Polymer Materials (Journal of Fiber Bioengineering and Informatics, 2018)
Polymers used in textiles were found to be effective as actuator materials with largedeformation. Particularly, the polymers with low dielectric constants used to be considered inactiveto electric field were turned out to be efficient actuator materials. They were classified into threetypes; (1) polymer gels swollen with solvents, (2) plasticized polymers, (3) bulk polymers. From theviewpoint of easy-to-operate, polymer gel deformation with swelling and deswelling was excludedhere. Swollen dielectric gels could be electrically deformed by solvent drag that induced asymmetricpressure distribution in the gels. Bending and crawling motions were observed in these materials. In thecase of plasticized polymers, especially in the case of poly(vinyl chloride) with plasticizers, amoebalikereversible creep deformation was found, and the strain with over several hundreds of percent wasdetected. The material was stable and could have been operated for over two years. Bulk polymerfilm like poly(ethylene terephthalate) was found to oscillate under an application of dc electric field.Of course, the Maxwell force induced elastic contractile deformation can be expected in all cases.The variation of the electrically induced deformation in dielectric polymer materials were demonstratedto be vast and expected application fields are also spread widely, particularly as artificial muscles.
Keywords: actuator; dielectric polymer; artificial muscle; polyethylene terephthalate; polyvinyl chloride; gels; plasticizer